2012
DOI: 10.2214/ajr.11.7957
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Pregnancy-Related Issues: Abnormal Placentation

Abstract: As abnormal placentation becomes more prevalent, in large part due to the markedly rising rates of cesarean delivery, there is a need for accurate antenatal diagnosis of this condition to prevent maternal morbidity and mortality. Maternal and fetal outcomes can be optimized through multidisciplinary planning to achieve accurate diagnosis and anticipation of the extent of abnormal placentation in the antenatal period. Imaging findings of abnormal placentation have been described for both ultrasound and MRI, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 50 publications
2
79
0
Order By: Relevance
“…Leyendecker and colleagues 2 agreed that these sequences reasonably differentiate between the placenta and myometrium, but available evidence suggests that it is difficult in practice. 2,33 Morita and co-workers 34 suggested that diffusionweighted (DW) sequences seems promising in evaluation of invasive placenta. 34 They reported that in DW images the placenta at a b-value of 1000 sec/mm 3 shows very high signal intensity, which enables clear identification of the placentaemyometrium interface.…”
Section: Nsa Rahaim Eh Whitby / Clinical Radiology XXX (2015) Ementioning
confidence: 99%
See 2 more Smart Citations
“…Leyendecker and colleagues 2 agreed that these sequences reasonably differentiate between the placenta and myometrium, but available evidence suggests that it is difficult in practice. 2,33 Morita and co-workers 34 suggested that diffusionweighted (DW) sequences seems promising in evaluation of invasive placenta. 34 They reported that in DW images the placenta at a b-value of 1000 sec/mm 3 shows very high signal intensity, which enables clear identification of the placentaemyometrium interface.…”
Section: Nsa Rahaim Eh Whitby / Clinical Radiology XXX (2015) Ementioning
confidence: 99%
“…Any focal bulging raises suspicion of invasion (Fig 4). 28,37 Leyendecker et al (2012) considered this imaging sign as the most useful criterion in isolation 2 ; however, this criterion is very specific but less sensitive as it exists only in the percreta cases. Furthermore, its diagnostic accuracy varied between studies as they were all small in size and the sensitivity depends on the number of percreta cases in each study.…”
Section: Abnormal Uterine Bulgingmentioning
confidence: 99%
See 1 more Smart Citation
“…9,30 Myometrial contractions consisting of transient, focal, ill-defined T2 hypointense thickening can also be seen. 31 The myometrium typically has a trilaminar appearance on T2-weighted or bSSFP images (Fig. 7A).…”
Section: Normal Mri Appearance Of the Placentamentioning
confidence: 99%
“…Of greater significance is localized bulging of the placenta and considered by some to be the most important sign of placenta accreta. 32 The placenta has a smooth contour; localized bulging or disruption of its otherwise smooth contour is very suggestive of a morbidly adherent placenta. Focal interruption of the myometrium is another useful sign of placenta accreta (Fig.…”
Section: Mri Signs Of Placenta Accretamentioning
confidence: 99%